Comparison of fasting and non-fasting serum lipid profile in healthy population - Mandle, K. S.; Prashant, Viplav; Sahu, Gopal K. (International Journal of Research in Medical Sciences, 2019)
Background: Serum lipids are routinely used for the assessment of cardiovascular risk. The test is usually performed under fasting condition. However, recently non-fasting lipid profile is also measured in certain cases. The present study was intended to estimate the concentration of total cholesterol (TC), triglyceride (TG), HDL cholesterol (HDL-C), LDL cholesterol (LDL-C) and VLDL cholesterol (VLDL-C) in fasting as well as non-fasting blood samples of a group of normal male and female subjects. Methods: The study recruited 50 normal healthy male and female subjects within the age group of 12-48 years. The concentration of TC, TG, HDL-C, LDL-C and VLDL-C in serum of these subjects were quantitatively determined using the commercially available kits based on CHOD/POD method. Results: The mean concentration of non-fasting TC, TG, HDL-C, LDL-C and VLDL-C was found to be 141.20 mg/dl, 132.20 mg/dl, 50.39 mg/dl, 64.30 mg/dl, 26.44 mg/dl respectively. On the other hand, the mean concentration of fasting TC, TG, HDL-C, LDL-C and VLDL-C was found to be 112.37 mg/dl, 100.90 mg/dl, 38.59 mg/dl, 53.59 mg/dl and 20.18 mg/dl respectively. The concentration of fasting lipid profile parameters was significantly low from the respective parameters of non-fasting lipid profile. Conclusions: The present study reveals that there was an increase in the levels of TC, TG, HDL-C, LDL-C, and VLDL-C in non-fasting state compared to the fasting state. Measuring the lipid profile parameters under non-fasting state cannot be usually considered for assessment of cardiovascular risk and for other clinical purposes.